Efectuati:
a) x supra√12 + √3 supra√5 + 4√135 supra 9 = 3√60 supra 5 + 3√20 supra √27
b) √3x + ( 5 - 2√3x ) * 2 supra √5 - 2 = √5 +2
c) x supra 1 supra √3 = √27 supra x
Răspunsuri la întrebare
Răspuns de
1
a) x/√12 + √3/√5 + 4√135/ 9 = 3√60/ 5 + 3√20 / √27
x√12/12 + √15/5 + 12√15/ 9 = 6√15/ 5 + 3√540/27
x√12/12 + √15/5 + 4√15/ 3 = 6√15/ 5 + 18√15/27
x√12/12= - √15/5 - 4√15/ 3 + 6√15/ 5 + 2√15/3
x√12/12= - 2√15/ 3 + 5√15/ 5
x√12/12= ( - 10√15 + 15√15)/ 15
x√12/12= 5√15/ 15
x√12/12= √15/3
x=√15/3 x12/√12
x=4√15/√12=4√180/12=√180/3=3√20/3=√20
b) √3x + ( 5 - 2√3x ) * 2/√5 - 2 = √5 +2
√3x + 10/√5 - 4√3x/√5 - 2 = √5 +2
√3x- 4√3x/√5 = √5 +2 - 10√5 +2
√3x - 4√3x/√5 = 4-9√5
√15x - 4√3x = 4√5-45
x(√15-4√3)= 4√5-45
x=(4√5-45 )/(√15-4√3)
c) x /(1/ √3) = √27 / x
x²=√27/√3=√9=3
x=+/-√3
x√12/12 + √15/5 + 12√15/ 9 = 6√15/ 5 + 3√540/27
x√12/12 + √15/5 + 4√15/ 3 = 6√15/ 5 + 18√15/27
x√12/12= - √15/5 - 4√15/ 3 + 6√15/ 5 + 2√15/3
x√12/12= - 2√15/ 3 + 5√15/ 5
x√12/12= ( - 10√15 + 15√15)/ 15
x√12/12= 5√15/ 15
x√12/12= √15/3
x=√15/3 x12/√12
x=4√15/√12=4√180/12=√180/3=3√20/3=√20
b) √3x + ( 5 - 2√3x ) * 2/√5 - 2 = √5 +2
√3x + 10/√5 - 4√3x/√5 - 2 = √5 +2
√3x- 4√3x/√5 = √5 +2 - 10√5 +2
√3x - 4√3x/√5 = 4-9√5
√15x - 4√3x = 4√5-45
x(√15-4√3)= 4√5-45
x=(4√5-45 )/(√15-4√3)
c) x /(1/ √3) = √27 / x
x²=√27/√3=√9=3
x=+/-√3
Alte întrebări interesante
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
b-√3
c- +-√3